Mayo imaging classification is a good predictor of rapid progress among Korean patients with autosomal dominant polycystic kidney disease: results from the KNOW-CKD study - Hayne Cho Park; Yeji Hong; Jeong-Heum Yeon; Hyunjin Ryu; Yong-Chul Kim; Joongyub Lee; Yeong Hoon Kim; Dong-Wan Chae; WooKyung Chung; Curie Ahn; Kook-Hwan Oh; Yun Kyu Oh (The Korean Society of Nephrology, 2022)
Background Mayo imaging classification (MIC) is a useful biomarker to predict disease progression in autosomal dominant polycystic kidney disease (ADPKD). This study was performed to validate MIC in the prediction of renal outcome in a prospective Korean ADPKD cohort and evaluate clinical parameters associated with rapid disease progression. Methods A total of 178 ADPKD patients were enrolled and prospectively observed for an average duration of 6.2 ± 1.9 years. Rapid progressor was defined as MIC 1C through 1E while slow progressor was defined as 1A through 1B. Renal composite outcome (doubling of serum creatinine, 50% decline of estimated glomerular filtration rate [eGFR], or initiation of renal replacement therapy) as well as the annual percent change of height-adjusted total kidney volume (mHTKV-α) and eGFR decline (mGFR-α) were compared between groups. Results A total of 110 patients (61.8%) were classified as rapid progressors. These patients were younger and showed a higher proportion of male patients. Rapid progressor was an independent predictor for renal outcome (hazard ratio, 4.09; 95% confidence interval, 1.23-13.54; p = 0.02). The mGFR-α was greater in rapid progressors (-3.58 mL/min per year in 1C, -3.7 in 1D, and -4.52 in 1E) compared with that in slow progressors (-1.54 in 1A and -2.06 in 1B). The mHTKV-α was faster in rapid progressors (5.3% per year in 1C, 9.4% in 1D, and 11.7% in 1E) compared with that in slow progressors (1.2% in 1A and 3.8% in 1B). Conclusion MIC is a good predictive tool to define rapid progressors in Korean ADPKD patients.